Effect of E-Service Quality on E-Customer Satisfaction Alfagift Application in West Java Province - Vida Wahda Maulida; Fitriani Nur Utami (Budapest International Research and Critics University, 2022)
The development of technology is now increasingly advanced, even for retail businesses that have used this technology. Utilization is done by making an online shopping application. Alfagift is an online shopping application owned by Alfamart. In 2020 Alfamart was ranked second with the largest number of outlets in Indonesia. The use of this technology certainly has a very positive impact on Alfagift, but in fact there are still some negative comments regarding the e-service quality of the Alfagift application. If this continues, e-customer satisfaction will also decrease. This study was conducted to determine the effect of e-service quality on e-customer satisfaction for Alfagift applications in West Java Province. This research uses quantitative methods with descriptive research types. Sampling was carried out using a non-probability sampling with purposive sampling with the number of samples used as many as 100 respondents. In this study, the population is all users who have transacted using the Alfagift application who are domiciled in West Java Province, the number of which is not known with certainty. The data analysis technique used is descriptive analysis and simple linear regression analysis. The test was carried out using the help of SPSS 25. Based on a partial hypothesis test, e-service quality had a significant effect on e-customer satisfaction for the Alfagift application in West Java Province. Based on the coefficient of simultaneous determination, it is found that e-service quality affects e-customer satisfaction by 51.8% and the remaining 48.2% is influenced by other factors not examined in this study.